Estructura horizontal de especies comerciales del bosque de terraza alta de la concesión forestal 16-REQ/C-J-190-04, distrito de Requena, Loreto. 2021 - Perez Serrano, Sergio Marti (2022)
The horizontal structure of commercial species of the high-terrace forest of forestry concession 16-REQ/C-J-190-04, district of Requena, Loreto, was determined. Data from the forest census of commercial species of PC1 for lumber purposes were evaluated. A total of 2,646 trees were registered, grouped into 32 commercial forest species and 13 botanical families. The Fabacea family contains the highest number of species (10 species). The distribution of the number of trees by diameter class is 1,53 trees/ha (2646 trees), where Cedrelinga cateniformis (0,29 trees/ha, 503 trees), Allantoma decandra (0,26 trees/ha, 372 trees), Parkia nitida (0.16 trees/ha, 272 trees), O. arborea (0,10 trees/ha, 179 trees) and Brosimum. rubescens (0,08 trees, 145 trees) show the highest number of trees. Cedrelinga cateniformis (Fabaceae) is the most ecologically important species with an IVI of 5125%, followed by Allantoma decandra (33,69%), Parkia nitida (23,35%), Ormosia arborea (15,87%) and Aniba panurensis (13,56%) The results show a highly significant difference between the averages of the horizontal structure between species.